2019
DOI: 10.18832/kp2019.65.158
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low-temperature plasma discharge on mycotoxin content in barley and malt

Abstract: This work deals with the possibility of elimination of common occuring mycotoxins deoxynivalenol (DON) and its plant metabolite deoxynivalenol-3-glucoside (D3G) from malting barley and malt by treatment of low-temperature plasma discharge. Barley seed was treated with a fungicide, entomopathogenic and mycoparasitic fungi and the low-temperature plasma discharge of Gliding Arc type, or their combination. Samples of harvested barley were treated with plasma discharge and analyzed for presence of mycotoxins. Only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have demonstrated DON and D3G contamination in barley [ 77 , 78 ], with a correlation between DON reduction and D3G formation in host plants and during food processing [ 77 ]. In contrast, a single study demonstrated that barley samples contaminated by DON and D3G experienced a significant reduction in the levels of both mycotoxins after NTAPP treatment [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated DON and D3G contamination in barley [ 77 , 78 ], with a correlation between DON reduction and D3G formation in host plants and during food processing [ 77 ]. In contrast, a single study demonstrated that barley samples contaminated by DON and D3G experienced a significant reduction in the levels of both mycotoxins after NTAPP treatment [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…Estudos anteriores demonstraram a contaminação por DON e D3G em cevada (Lancova et al, 2008;Maul et al, 2012), sendo observada uma correlação entre a redução de DON e formação de D3G em plantas hospedeiras e durante o processamento dos alimentos (Maul et al, 2012). Ademais, um único estudo demonstrou que amostras de cevada contaminadas por DON e D3G sofreram redução significativa nos níveis de ambas as micotoxinas, após o tratamento com PNT (Havelka et al, 2019). Kříž et al, (2015) tiveram resultados eficazes na redução de concentração de DON e D3G em sementes de cevada para malte usando dois tipos de plasma: plasma gerado por micro-ondas de baixa pressão e plasma de pressão atmosférica de descarga de arco deslizante.…”
Section: Efeito Do Pnt Na Micobiota Dos Grãos De Cevada Com Enfoque N...unclassified